2015
DOI: 10.12735/ier.v3i4p01
|View full text |Cite
|
Sign up to set email alerts
|

Children with Reading Disabilities and Outdoor Education

Abstract: This study explore if children with reading disabilities have differences in experiences and show different behaviors during indoor school and outdoor education in Norway. In the first study children with reading disabilities are compared with the rest of the classes in how they report wellbeing in different school settings. Thirty children participated in this study. In the second study the answers from the six children with various degrees of reading disabilities were analyzed further, and qualitative observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Outdoor Education can also impact the reduction of stress compared to indoor education. In this sense, a program that includes both environments could be evaluated as the stress accumulated during indoor activities could be released during outdoor activities without losing the basic focus which is the education of the students while continuing to contribute to their learning (Fiskum & Jacobsen, 2015). In a formal educational environment and also considering the training of support teachers, particular attention is provided by Information and communication technologies (i.e., ICT, TIC).…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor Education can also impact the reduction of stress compared to indoor education. In this sense, a program that includes both environments could be evaluated as the stress accumulated during indoor activities could be released during outdoor activities without losing the basic focus which is the education of the students while continuing to contribute to their learning (Fiskum & Jacobsen, 2015). In a formal educational environment and also considering the training of support teachers, particular attention is provided by Information and communication technologies (i.e., ICT, TIC).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, outdoor education has been found to reduce students' stress levels (Dettweiler, Becker, Auestad, Simon, & Kirsch, 2017), which might be important to reducing FLA. Research has also found that a change of environment may change the students' attitudes towards learning (e.g. Fiskum & Jacobsen, 2015;Skaugen & Fiskum, 2015). Fiskum and Jacobsen's (2015) study looked at children with reading disabilities, but still the findings might have relevance for young teenagers and their development of L2 fluency.…”
Section: Outdoor Educationmentioning
confidence: 99%
“…Fiskum & Jacobsen, 2015;Skaugen & Fiskum, 2015). Fiskum and Jacobsen's (2015) study looked at children with reading disabilities, but still the findings might have relevance for young teenagers and their development of L2 fluency. Several studies have also found that communication between learners is different in an outdoor environment than in a classroom setting (Fägerstam & Blom, 2013;Fiskum & Jacobsen, 2012a, 2012bMygind, 2014).…”
Section: Outdoor Educationmentioning
confidence: 99%
See 2 more Smart Citations